2012
DOI: 10.1063/1.3693609
|View full text |Cite
|
Sign up to set email alerts
|

A sintered nanoparticle p-n junction observed by a Seebeck microscan

Abstract: A nanoparticular p-n junction was realized by a field-assisted sintering process, using p-type and n-type doped silicon nanoparticles. A spatially resolved Seebeck microscan showed a broad transition from the positively doped to the negatively doped range. Overshoots on both sides are characteristic for the transition. Despite the tip size being much larger than the mean particle size, information about the dopant distribution between the particles is deduced from modeling the measured data under different ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Sharp property gradients are typically found in p–n or Schottky junctions, implying strongly localised depletion zones within their space charge regions, yielding a characteristic overshoot of the spatial Seebeck coefficient. Basically similar characteristics of thermopower whereas on a much wider local scale could be observed recently on sintered bulk materials from nanoscopic base powders 52. Microscanning by means of the Potential‐Seebeck Microprobe (PSM 53) mapped an overshooting S at the studied p–n region.…”
Section: Accuracy and Spatial Resolution Of Thermopower Probing Syssupporting
confidence: 64%
“…Sharp property gradients are typically found in p–n or Schottky junctions, implying strongly localised depletion zones within their space charge regions, yielding a characteristic overshoot of the spatial Seebeck coefficient. Basically similar characteristics of thermopower whereas on a much wider local scale could be observed recently on sintered bulk materials from nanoscopic base powders 52. Microscanning by means of the Potential‐Seebeck Microprobe (PSM 53) mapped an overshooting S at the studied p–n region.…”
Section: Accuracy and Spatial Resolution Of Thermopower Probing Syssupporting
confidence: 64%
“…Becker et al sintered films of microwave plasma-produced p - and n -type Si nanocrystals with doping concentrations of 5 × 10 20 cm –3 and 2 × 10 20 cm –3 , respectively . They used field-assisted sintering which makes use of pressure and of Joule heating to sinter the nanocrystals. , Using a Seebeck microscan technique, the authors observed a spatial spreading of the p- and n- type dopants in the sintered p–n junction. They interpreted this observation as a mixing of p- and n- type nanocrystals during the sintering process .…”
Section: Applicationsmentioning
confidence: 99%
“…They used field-assisted sintering which makes use of pressure and of Joule heating to sinter the nanocrystals. , Using a Seebeck microscan technique, the authors observed a spatial spreading of the p- and n- type dopants in the sintered p–n junction. They interpreted this observation as a mixing of p- and n- type nanocrystals during the sintering process . The consequent compensation of doping within the intermixing region reduced the charge carrier concentration at the interface.…”
Section: Applicationsmentioning
confidence: 99%
“…A temperature of 1200 °C is reached with a heating rate of 30 K min -1 and then held for 5 min. For more details about the preparation of the nanostructured pn junctions see references [22,23]. The densified p-n junction is cut to a geometry of 4 mm x 3 mm x 11 mm.…”
Section: Device Assemblymentioning
confidence: 99%